Treatment Benefit of Endovascular Therapy in MR CLEAN Quantified. Issue 2 (11th March 2015) - Kuznar, Wayne
An analysis of the treatment effect in the MR CLEAN study found that for every 100 patients with large vessel acute ischemic stroke treated with endovascular therapy, 14 will not have a disability and 23 to 32 will have a lesser degree of disability compared with that of medical therapy.